Effects of long-term biochar application combined with chemical fertilization on the nitrifier community in tobacco plantation soil - Xu, Di; Luo, Hang; He, Tianyi; E, Yang; Gao, Junyi (Frontiers in Microbiology, 2025)
Soil nitrogen (N) plays a critical role in plant nutrition and is regulated by the process of nitrification. Biochar can enhance soil N concentration and is hypothesized to influence nitrification, particularly when applied in combination with chemical fertilizers. Although, several studies have documented the effects of biochar and fertilizer combinations on nitrifying microbial communities, the underlying mechanisms remain poorly understood. In this study, the abundances of ammonia-oxidizing archaea (AOA) in the BT3 (15 t/ha) and BT5 (40 t/ha) treatments, and ammonia-oxidizing bacteria (AOB) in the BT4 (20 t/ha) treatment, were significantly higher than in fertilizer-only treatments. In contrast, nitrite-oxidizing bacteria (NOB) in the BT2 (5 t/ha) treatment exhibited the most significant difference (p < 0.05). Compared to the control (BT1), the relative abundances of AOB (Nitrosomonas; 51.74%) and NOB (Nitrolancea; 62.26%) increased significantly (p < 0.05) with higher application rates of biochar fertilizer concentration. Metabolic profiling and molecular docking simulations precisely demonstrated that 2,2-diethylacetamide (DEA), a compound structurally analogous to oxalate, interacts with the active site of pyruvate kinase, thereby affecting the glycolysis pathway. A subsequent potting experiment confirmed that DEA treatment increased pyruvate kinase gene expression (from 1.37 to 11.03; p < 0.05), soil pyruvic acid concentration (from 1.73 to 21.65; p < 0.05), and nitrifier abundance (from 0.20% to 0.56%; p < 0.05). Furthermore, soil copper (Cu; R2 = 0.21, p < 0.05), molybdenum (Mo; R2 = 0.53, p < 0.05), zinc (Zn; R2 = 0.37, p < 0.05), and total organic carbon (TOC; R2 = 0.24, p < 0.05) content were negatively correlated with nitrifier abundance as biochar-fertilizer application increased. This indicates that DEA derived from biochar, in conjunction with soil elemental composition, collectively influences nitrifying communities. The relationships between biochar-fertilizer application and nitrifier communities established in this study will inform precise application strategies to enhance nitrogen use efficiency in crops.